1976
DOI: 10.2135/cropsci1976.0011183x001600030026x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Percent Total Alkaloids and Other Traits in Flue‐cured Tobacco1

Abstract: The relationships between percent total alkaloids and nine agronomic and chemical traits were studied in isogenic lines derived from 10 cultivars of flue‐cured tobacco (Nicotiana tabacum L.). Isogenic lines with low total alkaloids percentage (approximately 0.20%) were compared with their “normal” recurring parents (total alkaloids 1.85 to 2.70%). The differences in traits other than alkaloid levels between the low alkaloid lines and their recurrent parent should reflect physiological associations (pleiotropis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 0 publications
2
22
0
1
Order By: Relevance
“…A typical objective of metabolic engineering is to achieve a desired chemical change without otherwise affecting other chemical attributes, growing efficiency, or derived product quality. Prior research has revealed great difficulty in using modified plant genetics to reduce nicotine levels without altering metabolic profiles or negatively affecting tobacco cured leaf yields or quality (Chaplin and Weeks, 1976;Kudithipudi et al, 2017). Similar to the nic1/nic2 system of nicotine reduction, the BBL mutant system was also found to reduce cured leaf yields by up to 29%, with associated reductions in cured quality of up to 15%.…”
Section: Combining Bbl Mutations With Recessive Alleles At the Nic1 Amentioning
confidence: 99%
See 1 more Smart Citation
“…A typical objective of metabolic engineering is to achieve a desired chemical change without otherwise affecting other chemical attributes, growing efficiency, or derived product quality. Prior research has revealed great difficulty in using modified plant genetics to reduce nicotine levels without altering metabolic profiles or negatively affecting tobacco cured leaf yields or quality (Chaplin and Weeks, 1976;Kudithipudi et al, 2017). Similar to the nic1/nic2 system of nicotine reduction, the BBL mutant system was also found to reduce cured leaf yields by up to 29%, with associated reductions in cured quality of up to 15%.…”
Section: Combining Bbl Mutations With Recessive Alleles At the Nic1 Amentioning
confidence: 99%
“…Recessive alleles at the Nic1 and Nic2 (also known as A and B) loci have been found to contribute to major reductions in nicotine and associated alkaloids (nornicotine, anabasine, and anatabine) from between 1.5 and 4.5% to approximately 0.20-0.45% (Legg and Collins, 1971;Lewis, 2018). This allelic variability is well known to be associated with reduced cured leaf yields and quality, however (Chaplin and Weeks, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Brown pigments and total phenols are known to play a role in the color of cured tobacco leaves (Andersen et al, 1970). It is also possible that total alkaloids influence the color of tobacco leaves based on the report of Chaplin and Weeks (1976) and the visual observations of Gupton et al ( 1972) that indicated an increased wood color of burley tobacco stalk cross sections was associated with higher leaf alkaloid levels for samples from tobaccos of divergent alkaloid genotype. Nitrate-N presumably does not affect color directly, but it is a biochemical precursor of alkaloids.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…LA Burley 21 plants contain only~5.7% of the total alkaloid levels found in the normal-alkaloid (NA) wild-type variety (Legg, Collins, & Littion, 1970). In LA plants, the synergistic effect of the nic1 − and nic2 − deletions also causes an unfavorable leaf phenotype characterized by lower yields, delayed ripening and senescence, higher susceptibility to insect herbivory, and poor end-product quality after curing (Chaplin & Burk, 1983;Chaplin & Weeks, 1976;Legg et al, 1970). A better understanding of the differences between LA and NA plants could facilitate strategies to improve the quality of LA leaf and its resulting tobacco products and allow the development of new tobacco cultivars with lower alkaloid levels combined with comparable or superior product characteristics.…”
Section: Introductionmentioning
confidence: 99%